2012
DOI: 10.1590/s0100-40422012000700027
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for treatment and reuse of spent sulfidic caustic stream from petroleum industry

Abstract: Recebido em 19/8/11; aceito em 7/2/12; publicado na web em 15/6/12 This work examines traditional and new routes for removal of H 2 S and other sulfur compounds from spent sufidic caustic (SSC). SH -(hydrogenosulfide) and S 2-(sulfide) ions were quantitatively oxidized at 25 ºC using H 2 O 2 , NaOCl or a spent sulfochromic mixture. SH -/S 2-ions were also removed via reaction with freshly prepared iron or manganese hydroxides, or after passing the SSC through strong basic anion exchange resins (OH -form). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The experiments were performed by adjusting the temperature (ranging from 25 to 40 °C), pH (8)(9)(10)(11), sodium chloride (0.5-5 % w/v), and sodium thiosulfate (100-750 mM). For the preparation of the mentioned pH range (8, 9, 9.5, 10, 10.5, 11), a set of carbonate buffers containing 2 M Na + was used.…”
Section: Cultivation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments were performed by adjusting the temperature (ranging from 25 to 40 °C), pH (8)(9)(10)(11), sodium chloride (0.5-5 % w/v), and sodium thiosulfate (100-750 mM). For the preparation of the mentioned pH range (8, 9, 9.5, 10, 10.5, 11), a set of carbonate buffers containing 2 M Na + was used.…”
Section: Cultivation Experimentsmentioning
confidence: 99%
“…Spent caustic is one of the most complicated and hazardous wastewaters produced in various gas and oil sweetening processes in refineries and petrochemical plants [3,[6][7][8]. Although characteristics of spent caustics may greatly vary from a refinery to another, these wastewaters are generally studied in three different categories namely sulfidic, phenolic and naphthenic [6,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawback of such ion-exchange resin is that it has limitedhydrophilic character which is in separation application, such resin useful for retention non-polar compound only and have low specific surface area (SSA). Gel-type resin have higher (SSA) (>1000 m 2 /g) [1] 9,10 and macroporous structure have lower than 600 m 2 /g.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that positive charges in resin have potential to be used in many applications. For example, in sulfur removal, 1 phosphorus removal in wastewater, 2 separation of actinides elements in sediments and biological materials, 3 and even be used to decrease the acid value of crude low-calorie cocoa butter to an acceptable level. 4 Most of the strong anion resins used in the studies is commercially available.…”
Section: Introductionmentioning
confidence: 99%